Effect of Serial Passage on Growth Kinetics, Biological Properties, and Differentiation into Adipocytes of Human Wharton’s Jelly-Derived Mesenchymal Stem Cells (Majalah Kedokteran Bandung, 2019)
Early passges of human Wharton’s jelly-derived mesenchymal stem cells (hWJMSCs) have been suggested by various studies; however, the effect of serial passaging has not been well defined. This study aimed to investigate the effect of serial passage on the growth kinetics, biological properties and differentiation into adipocytes on hWJMSCs. This study was conducted from April to December 2014 to evaluate the hWJMSCs growth kinetics at passage 6 (P6) and P12 by calculating proliferation rate, population doubling time (PDT), and cumulative population-doubling levels (CPDL) using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium MTS assay kit. The cells biological properties were characterized using flow cytometry analysis followed by measuring the differentiation into adipocytes in extensive culture using Oil Red O staining after induction. An independent sample t-test was applied to analyze the differences between groups using IBM SPSS Statistics Version 22 with a p
Keywords: differentiation into adipocytes; serial passage; stem cells; Wharton jelly